JUSTIFICATION OF DIRECTIONS FOR IMPROVING AUTHENTICATION PROTOCOLS IN INFORMATION AND COMMUNICATION SYSTEMS - Havrylova, Alla; Khokhlachova, Yuliia; Tkachov, Andrii; Voropay, Natalia; Khvostenko, Vladyslav (Ukrainian Information Security Research Journal, 2023)
The analysis of information about the conducted cyber-threats makes it possible to identify modern information security problems when transmitted through unprotected communication channels. When conducting such an analysis, various components of the methods of implementing cyber threats are considered, but in this paper, it is proposed to pay attention to the motivational component of the emergence of threats and the existing effective tools for countering them. Such a comprehensive approach will make it possible to predict various modes of cyberattacks that cybercriminals can use against certain systems and to prepare the necessary digital security systems for the implementation of future threats. The influence of the exponential growth of the capacities of computing devices on the growth of the possibilities of implementing attacks by cybercriminals on cryptographic algorithms was also revealed. In this regard, the work considered the possibilities of increasing the level of resistance to such interventions, which are ensured by the NIST requirements for stability and security in the conditions of the post-quantum period. To determine the level of security of data transmission over an insecure network with privacy, integrity and authentication, a comparative analysis of the capabilities of information transmission protocols was conducted. The results of the analysis are presented in the form of a scheme of security and stability of protocols and algorithms that made it to the finals of the NIST competition. To ensure the integrity and authenticity of users when establishing communication sessions with websites, it is recommended to use TLS protocols. A scheme of the process of authenticated encryption and verification of the authenticity of an encrypted message transmitted using a TLS connection has been developed. The process diagram of authentication encryption and decryption of information when establishing a communication session in TLS protocols has been developed. A comparative analysis of different versions of TLS protocols was carried out.